2013
DOI: 10.1192/s1749367600003714
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards sexual minorities among Chinese people: implications for mental health

Abstract: Heterosexuality continues to be regarded and adopted as a norm in the majority of Asian societies. In Hong Kong, lesbians and gay men are still encountering unfavourable attitudes from the general public (such as stereotyping and discrimination). This paper briefly reviews the legal and cultural context and notes in particular the situation in schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Previous studies have already verified that due to homosexual individuals' sexuality, the rejection from their family and peer bullying in childhood are closely linked to their mental health status in adulthood (Earnshaw et al, 2016;Ryan et al, 2009;Wang et al, 2018). Similar to the worldwide cases, the hostility, stigma and discrimination against sexual minorities is prevalent in China as well (Wu & Kwok, 2013). And because of the traditional Chinese Confucian culture, marriage and reproduction are seen as an unalterable obligation to continue family bloodline, which means that gay men in China might suffer more pressure and stress to get married (Hesketh et al, 2005;Yu et al, 2011).…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies have already verified that due to homosexual individuals' sexuality, the rejection from their family and peer bullying in childhood are closely linked to their mental health status in adulthood (Earnshaw et al, 2016;Ryan et al, 2009;Wang et al, 2018). Similar to the worldwide cases, the hostility, stigma and discrimination against sexual minorities is prevalent in China as well (Wu & Kwok, 2013). And because of the traditional Chinese Confucian culture, marriage and reproduction are seen as an unalterable obligation to continue family bloodline, which means that gay men in China might suffer more pressure and stress to get married (Hesketh et al, 2005;Yu et al, 2011).…”
Section: Introductionmentioning
confidence: 89%
“…The studies of Collier et al (2012), Detenber et al (2013), Feng et al (2012), Lau et al (2014) and Tu and Lee (2014) show that an individual’s intimate interaction with a homosexual person is one of the factors contributing to the negative behaviour towards homosexuality. The studies by Besen and Zicklin (2007), Cardenas et al (2012), Ng et al (2015), Wu and Kwok (2013) and Yen et al (2007) found that religion is another negative contributing factor. The studies by Cardenas et al (2012), Feng et al (2012) and Wellman and McCoy (2014) found that traditional gender roles are another mental prison people have when it comes to their perception of homosexuality.…”
mentioning
confidence: 98%